Island affair - Oliveras, Priscilla (Oliveras, Priscilla. Keys to love, 2023)
"Sought-after social media influencer Sara Vance, in recovery from an eating disorder, is coming into her own, with a potential career expansion on the horizon. Despite the good news, her successful siblings (and their perfect spouses) have a way of making her feel like the odd one out. So, when her unreliable boyfriend is a no-show for a Florida family vacation, Sara recruits Luis Navarro - a firefighter paramedic and dive captain willing to play the part of her smitten fiancé ... Luis's big Cuban familia has been in Key West for generations, and his quiet strength feeds off the island's laidback style. Though guarded after a deep betrayal, he'll always help someone in need - especially a spunky beauty with a surprising knowledge of Spanish curse words. Soon, he and Sara have memorized their "how we met" story and are immersed in family dinners, bike tours, private snorkeling trips . . . sharing secrets, and slow, melting kisses. But when it's time for Sara to return home, will their fake relationship fade like the stunning sunset . . . or blossom into something beautiful?"--Back cover.